2017
DOI: 10.2147/opth.s148467
|View full text |Cite
|
Sign up to set email alerts
|

Resident-performed laser peripheral iridotomy in primary angle closure, primary angle closure suspects, and primary angle closure glaucoma

Abstract: PurposeTo investigate the power use and complication frequency of resident-performed laser peripheral iridotomy (LPI).MethodsA retrospective analysis of 196 eyes from 103 patients who underwent neodymium: yttrium-aluminum-garnet laser iridotomy performed by resident physicians from January 1, 2010 through April 30, 2015 at a university-based county hospital was done. All patients were treated for primary angle closure, primary angle closure suspects, and primary angle closure glaucoma. Data were collected on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(36 citation statements)
references
References 18 publications
1
33
2
Order By: Relevance
“…17 However, the literature has identified Asian ethnicity as an independent prognostic factor for increasing the likelihood of requiring RPs. 9,18 When analyzing our data on ethnicity and RP rates, we observed no statistical significance, likely because of the small non-Caucasian population of the study (2%), which is representative of the local population, but differs from demographic data documented in other studies that have observed this difference. 9 The difference in RP rate for Asian ethnicity observed in other literature is believed to be due to greater laser-energy requirement to penetrate the iris to perform an iridotomy on the thicker dark-brown irides, more common in the Asian population.…”
Section: Discussioncontrasting
confidence: 75%
“…17 However, the literature has identified Asian ethnicity as an independent prognostic factor for increasing the likelihood of requiring RPs. 9,18 When analyzing our data on ethnicity and RP rates, we observed no statistical significance, likely because of the small non-Caucasian population of the study (2%), which is representative of the local population, but differs from demographic data documented in other studies that have observed this difference. 9 The difference in RP rate for Asian ethnicity observed in other literature is believed to be due to greater laser-energy requirement to penetrate the iris to perform an iridotomy on the thicker dark-brown irides, more common in the Asian population.…”
Section: Discussioncontrasting
confidence: 75%
“…These logs could be reviewed by an attending ophthalmologist and feedback provided to the residents. At our institution, once this curriculum has been given for a few consecutive years, it is our hope to conduct a follow-up study to the one published by Kam and colleagues 6 to assess for improvements in LPI proficiency.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 The University of Washington recently reviewed all residentperformed LPIs over a 5-year period and found that while total energy use and complication rates were comparable to attending-performed LPIs in the literature, there was a higher incidence of repeat laser to reopen or enlarge peripheral iridotomies. 6 In an effort to standardize LPI teaching and decrease the incidence of repeat LPI, as well as to help maintain minimal complication rates, an LPI curriculum including a lecture and a skills practice session was introduced.…”
Section: Citationmentioning
confidence: 99%
See 1 more Smart Citation
“…Preventative laser iridotomies are currently performed in most patients with narrow anterior chamber angles; the prevalence of this condition in adults varies from 0.7–10% depending on race 710. In addition, given the growing frequency of patients taking antiplatelet or anticoagulant agents, the number of patients requiring a laser iridotomy is increasing.…”
Section: Discussionmentioning
confidence: 99%